2018
DOI: 10.1371/journal.pone.0202134
|View full text |Cite|
|
Sign up to set email alerts
|

Divalent cation and chloride ion sites of chicken acid sensing ion channel 1a elucidated by x-ray crystallography

Abstract: Acid sensing ion channels (ASICs) are proton-gated ion channels that are members of the degenerin/epithelial sodium channel superfamily and are expressed throughout central and peripheral nervous systems. ASICs have been implicated in multiple physiological processes and are subject to numerous forms of endogenous and exogenous regulation that include modulation by Ca2+ and Cl- ions. However, the mapping of ion binding sites as well as a structure-based understanding of the mechanisms underlying ionic modulati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 36 publications
4
44
1
Order By: Relevance
“…A Cl − binding site in close proximity of residue 212 was found in the open and desensitized but not in the closed ASIC1a structure (Jasti et al, 2007; Gonzales et al, 2009; Baconguis and Gouaux, 2012; Baconguis et al, 2014; Yoder and Gouaux, 2018; Yoder et al, 2018). It was shown that the chloride concentration affects the ASIC current decay kinetics (Kusama et al, 2010, 2013), and that mutations of the predicted Cl − binding site disrupted the modulation of the current decay kinetics if introduced in ASIC1a (Kusama et al, 2010), and had a partial, or no effect if introduced into ASIC2a or ASIC3, respectively (Kusama et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…A Cl − binding site in close proximity of residue 212 was found in the open and desensitized but not in the closed ASIC1a structure (Jasti et al, 2007; Gonzales et al, 2009; Baconguis and Gouaux, 2012; Baconguis et al, 2014; Yoder and Gouaux, 2018; Yoder et al, 2018). It was shown that the chloride concentration affects the ASIC current decay kinetics (Kusama et al, 2010, 2013), and that mutations of the predicted Cl − binding site disrupted the modulation of the current decay kinetics if introduced in ASIC1a (Kusama et al, 2010), and had a partial, or no effect if introduced into ASIC2a or ASIC3, respectively (Kusama et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, SMA-cASIC1a particles maintained at pH 8.0 occupy a high pH resting conformation, characterized by an expanded acidic pocket (Figure 1G) that resembles the high pH, resting state structures solved by x-ray crystallography and single particle cryo-EM (27). We propose that the limited resolution of the resting channel structure, while presumably impacted by sample conditions including thicker ice, may also be due to structural flexibility inherent to the resting channel conformation in the absence of divalent cations, which serve to stabilize an expanded acidic pocket at high pH (40) but which are incompatible with current SMA-based purification strategies.…”
Section: Resultsmentioning
confidence: 99%
“…Only ASIC2b does not form functional homomeric channels [87]. One subunit consists of two transmembrane domains, having both the N- and C-termini at the intracellular side [88,89]. Most of the protein is located at the extracellular side forming the large extracellular domain (termed ECD).…”
Section: Ion Channels As Targets Of Gpcr Signaling In Peripheral Nmentioning
confidence: 99%
“…ASIC channels follow a three-state kinetic model, from a closed to an activated to an inactivated state. The recovery from inactivation can only be achieved in high pH conditions [88] and this desensitized state is thought to be regulated by the thumb domain within the ECD [90].…”
Section: Ion Channels As Targets Of Gpcr Signaling In Peripheral Nmentioning
confidence: 99%